A Comparative Performance Analysis of Four Wind Turbines with Counter-Rotating Electric Generators - Neagoe Mircea; Saulescu Radu; Jaliu Codruta; Munteanu Olimpiu; Cretescu Nadia (MDPI, Basel, Switzerland, 2022)
Wind energy conversion systems play a major role in the transition to carbon-neutral power systems, and obviously, a special attention is paid in identifying the most effective solutions for a higher valorization of the local wind potential. In this context, this paper presents a comparative study on the energy performances of wind turbines (WTs) that include a counter-rotating electric generator. Starting from an innovative concept proposed by the authors for a reconfigurable wind turbine with three clutches, four cases of WTs with counter-rotating generators are studied: a system with three wind rotors (WRs) and a 2-DOF (degrees of freedom) planetary speed increaser (Case A), with two counter-rotating WRs and a 1-DOF (Case B) or a 2-DOF (Case C) speed increaser and a 1-DOF single rotor wind system (Case D). An analytical archetype model for angular speeds, torques, powers and efficiency of the reconfigurable planetary speed increaser, corresponding to the general case with three inputs (Case A), was firstly derived. The analytical models of the other three cases (B, C and D) were results by customizations of the archetype model according to the kinematic- and static-specific effects of engaging/disengaging the clutches. The simulation of the analytical models for a numerical representative example with two variable parameters (input speed ratio 𝑘ω and input torque ratio 𝑘𝑡 ) allows highlighting the influence of various parameters (number of WRs, speed increaser DOF, 𝑘ω and 𝑘𝑡 ) on the input powers, power that flows through the planetary transmission and mechanical power supplied to the electric generator, as well as on the transmission efficiency. The obtained results show that the output power increases with the increase of the number of wind rotors, the transmission efficiency is the maximum for 𝑘𝑡=1 and the speed amplification ratio increases with the ratio 𝑘ω.
Keywords: renewable energy; wind turbine; wind rotor; counter-rotating electric generator; speed increaser; steady-state modeling; efficiency; power flow